Strength of structural timber members with finger-joints and metal plate connectors - Yeoh, David Eng Chuan (1999)
Finger jointing of short off-cuts for structural purposes particularly for lightweight roof truss and prefabricated timber house is likely an economical method of minimizing waste and generating benefits. The primary goal of this research is on the possibility of using finger-jointed timber with metal plate connectors for structural purposes, i.e. in trusses: internal members, top and bottom chord. This research assessed the strength properties of finger-jointed strength group B timber and the influence of number of joints and its positioning on strength. The glue applied for finger jointing is polymer isocyanate adhesive or commercially known as Koyo glue. Bending, compression and tension tests were carried out and the results show that the efficiency of the joints in relation to the strength of the unjointed specimens were greatly influenced by the positioning and number of joints. The results obtained from tests indicated that modulus of rupture decreases with the presence of finger joint while modulus of elasticity is not affected. Tests on the performance of connection with metal plate using finger-jointed timber showed small difference in the basic working load as compared to the unjointed specimens. The study suggests that the combination use of finger-jointed timber with metal plate connector for structural purposes is acceptable depending on the joint efficiency, the position and number of the finger joint in the member, and the type of stresses (i.e. compression, tension or bending) in the member.